Genomic insights from Lactiplantibacillus plantarum BRD3A isolated from Atingba, a traditional fermented rice-based beverage and analysis of its potential for probiotic and antimicrobial activity against Methicillin-resistant Staphylococcus aureus - Huidrom, Surmani; Ngashangva, Ng; Khumlianlal, Joshua; Sharma, Kongbrailatpam Chandradev; Mukherjee, Pulok Kumar; Devi, Sarangthem Indira (Frontiers in Microbiology, 2024)
Lactiplantibacillus plantarum BRD3A was isolated from Atingba, a traditional fermented rice-based beverage of Manipur. Its genomic sequence has 13 contigs and its genome size is 3,320,817 bp with a guanine–cytosine (GC) ratio of 44.6%. It comprises 3185 genes including 3112 coding sequences (CDSs), 73 RNAs (including 66 tRNAs and others), and one clustered regularly interspaced short palindromic repeat (CRISPR) array. A comparative and phylogenetic analysis with the Lp. plantarum genome shows that this strain has close similarity with other Lp. plantarum strains and about 99% average nucleotide identity. Functional annotation using evolutionary genealogy of genes—non-supervised orthologous groups (EggNOG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) reveals genes associated with various biological processes such as metabolism, genetic information processing, and transport functions. Furthermore, the strain harbors bacteriocins like plantaricin E, Plantaricin F, and Enterocin X categorized under class IIb by the BAGEL4 database, indicating its potential antimicrobial properties. Additionally, AntiSMASH web server predicted four secondary regions—T3PKS, terpene, cyclic lactone inducer, and ribosomally synthesized and post-translationally modified peptide (RiPP)—suggesting an even higher antimicrobial potential. We validated the antimicrobial activity of Lp. plantarum BRD3A through in vitro experiments in which it exhibited promising bactericidal effects on methicillin-resistant Staphylococcus aureus, inhibiting their biofilm growth. These findings indicate the potential of Lp. plantarum BRD3A to be used as an alternative to conventional antibiotics.